RANCANGAN ALAT PEMBUATAN BIOETANOL DARI BAHAN BAKU KULIT DURIAN - Irvan; Bambang Trisakti; Luri Adriani; Reviana Revitasari (Jurnal Teknik Kimia USU, 2015)
In this research, the bioethanol production unit using durian peel as raw material was designed with capacity process of 100 liters per cycle in batch process. The main equipments were designed fermenter and distillation unit. Fermenter tank was designed with 43 cm of diameter and 86 cm of height which was equipped with two manual paddle impeller of 30 cm in diameter. The other of main equipments, distillation tank was made of stainless steel with 48 cm of diameter and 54 cm of height, which was equipped with heater to heat the liquid of fermentation process and cooling tank to cool vaporised bioethanol. The time required for one cycle of fermentation with batch process was 7 days and 7 hours. While the time required for one cycle of bioethanol production with batch process was 8 days and 4 hours. The feasibility of bioethanol production unit in which consists of fermenter tank and distillation tank under condition process of 7 days and yeast concentration of 6% and distillation temperature of 80oC was tested. The results obtained were 8,98% of bioethanol concentration during fermentation and 74,96% of bioethanol concentration during distillation.